BILATERAL CONGENITAL CATARACT IN A NEWBORN- LITERATURE REVIEW AND CASE REPORT - Isjanovski, Igor; Pandilov, Stefan; Dashtevska, Emilija Gjosevska (Journal of Morphological Sciences, 2023)
Congenital cataract is the leading cause of childhood blindness. The etiology for its occurrence can be different: metabolic diseases, genetic factors, infectious agents, but mostly idiopathic. The purpose of this paper is to present a case of congenital cataract in a 10-day-old infant who presented with leukocoria in the first days of life, as well as to provide an overview of modern diagnostic and therapeutic modalities in the management of this ophthalmic condition. In the preparation of this topic, medically relevant data obtained from three large databases were used: PubMed, Embase and Scopus. Keywords such as: congenital cataract, newborn, leukocoria, red reflex were used during the search. The obtained data were selected and processed, while the latest and most relevant knowledge from this field was included in the preparation of this paper. Rapid recognition of this condition is important in order to preserve good visual function and avoid the potential complications of its presence: deprivation amblyopia, strabismus, nystagmus and glaucoma.  Keywords: congenital cataract, leukocoria, red reflex, newborn.